Analisis Hukum Islam Terhadap Praktik Akad Istishna - Junaidy, Athailah; Yusriadi, Yusriadi (Al-Hiwalah: Journal of Sharia Economic Law, 2022)
This research is entitled "Analysis of Islamic Law Against the Practice of Istishna Contracts'". In it examines the practice of istiṣna 'contracts. Istiṣna' contract is a sale and purchase with an order and one of the forms of buying and selling that is often applied by the public. In general, the buyer comes to the seller to ask for an item that does not yet have a form. The problem in this study is how the practice of buying and selling orders that occurs in Hawe Furniture, and whether the practice of buying and selling orders that occurs in Hawe Furniture is in accordance with existing Islamic law. The purpose of this study was to determine the concept of Islamic law on buying and selling orders and to find out the practice of buying and selling orders at Hawe Furniture. This research method is qualitative with inductive data analysis. The results of this study indicate that buying and selling orders that occur at Hawe Furniture are in accordance with Islamic law, where the transaction contract that occurs between the seller and the buyer has an agreement on the price and payment system, then the seller records it to find out the name of the customer, the ordered goods, the money received. has been paid and the time of delivery of the goods is adjusted from the contract that has been agreed between the two parties.